Grouping of Experimental Conditions as an Approach to Evaluate Effects of Extremely Low-Frequency Magnetic Fields on Oxidative Response in in vitro Studies - Mattsson, Mats-Olof; Simkó, Myrtill (Frontiers in Public Health, 2014)
A large body of literature deals with biological effects of extremely low frequency magnetic fields (ELF MF) studied in vitro. Despite the multitude of studies, no coherent picture has evolved regarding the plausibility of effects at low flux densities or regarding the interaction mechanisms. Here we propose that ELF MF exposure in vitro causes changes in oxidative status as an early response. We tested this hypothesis by scrutinizing the literature and applying a grouping approach for analyzing relevant biological properties and exposure conditions. A total of 41 scientific original publications were analyzed for this purpose. The conclusion from the work is that ELF MF (modulated or unmodulated) consistently can influence the oxidative status, at or above 1 mT, in a broad range of cell types and independent of exposure duration. A response at lower flux densities is seen in certain studies, although not consistently. Further studies with stringent protocols for sham exposure, blinding, and statistical analysis as well as appropriate positive controls are needed to establish if true dose-relationships for effects on oxidative status exist.